2008
DOI: 10.1093/ajcn/87.5.1121
|View full text |Cite
|
Sign up to set email alerts
|

Overweight children find food more reinforcing and consume more energy than do nonoverweight children

Abstract: These results show that overweight children find food more reinforcing than do nonoverweight children. This individual difference was replicated in different experiments using different types of foods and food alternatives. These studies provide support for studying food reinforcement as a factor associated with overweight and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
189
4
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(207 citation statements)
references
References 33 publications
(46 reference statements)
11
189
4
3
Order By: Relevance
“…Specifically, non-obese individuals who were low in baseline food reinforcement were more likely to sensitize to repeated food exposure, but obese individuals who were high in baseline food reinforcement were more likely to sensitize than obese people who were low in baseline food reinforcement. Although many studies have demonstrated a relationship between weight status and food reinforcement, 4,5,31 ours are among the first to show an increase in food reinforcement or food 'wanting' after repeated intake of a high energy density snack food. The interaction between BMI and baseline level of motivation to eat suggests that there is a difference in what is driving sensitization in these two populations.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Specifically, non-obese individuals who were low in baseline food reinforcement were more likely to sensitize to repeated food exposure, but obese individuals who were high in baseline food reinforcement were more likely to sensitize than obese people who were low in baseline food reinforcement. Although many studies have demonstrated a relationship between weight status and food reinforcement, 4,5,31 ours are among the first to show an increase in food reinforcement or food 'wanting' after repeated intake of a high energy density snack food. The interaction between BMI and baseline level of motivation to eat suggests that there is a difference in what is driving sensitization in these two populations.…”
Section: Discussionmentioning
confidence: 58%
“…2,3 In addition, obese individuals find food more reinforcing than non-obese individuals. 4,5 Although food reinforcement is a relatively stable trait, it can be modified depending on the context or types of foods that are used. Food deprivation and food variety reliably increase the reinforcing value of food 6 --9 and high-fat, palatable foods are more reinforcing than healthier, low-fat alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Parents may use food to comfort the highly soothable infant, which may over time enhance the reinforcing properties of foods. 65,66 Future research should explore such reciprocal behavioral mechanisms. Increased food reward has been linked to obesity status in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Increased food reward has been linked to obesity status in children and adults. 65,67 Another possibility is that highly soothable girls are comforted more easily by watching television, which parents might then encourage. Increased television viewing has been linked to high-calorie snack food consumption [68][69][70] and increased obesity risk.…”
Section: Discussionmentioning
confidence: 99%
“…The reward circuitry in the brain is predominantly underpinned by neurotransmission of dopamine and endogenous opioids in the striatum (Lutter & Nestler, 2009), but there is considerable overlap and cross-talk between reward signalling and feeding centres in the hypothalamus (Berthoud, 2004). Gene polymorphisms relating to reward function could infl uence eating behaviour by amplifying the motivation to eat (Temple et al, 2008), altering sensory/hedonic perception of food (Davis et al, 2011), or via weak satiety responsiveness .…”
Section: Adrenergic Receptor Gene Variants -A Role In Polygenic Obesimentioning
confidence: 99%